Family empowerment as an effort to prevent hypertension in the adolescent group in the working area of the Kebonsari Health Center Surabaya - Siti Nur Kholifah; M. Minarti; Heru Sulistijino; Ferry Kumala (Journal of Community Service and Empowerment, 2022)
Hypertension in adolescents is increasing in Indonesia, including in East Java. An unhealthy lifestyle, activity, eating less vegetables and fruits and increasing smoking habits are the causes of the increasing prevalence of hypertension in adolescents. This condition is a big problem, because the incidence of hypertension in adolescence will continue in adulthood and have a higher risk of morbidity and mortality. This service activity aims to identify the role of the family in preventing hypertension in adolescents before and after the empowerment process, as well as identifying family behavior to prevent hypertension after the empowerment process. The method used is an empowerment intervention to the family. The result of this empowerment activity is that the empowerment that has been carried out can increase the role of the family in preventing the occurrence of hypertension in adolescents. The empowerment process is carried out through the activities of providing health education, mentoring, and monitoring the increase in the role of the family.